Respuesta :
[tex]\qquad \sf \: \huge \bf༆ Answer ༄[/tex]
Here's the solution ~
[tex]\qquad \sf \dashrightarrow \: f(x) = \tan(x) [/tex]
[tex]\qquad \sf \dashrightarrow \: f(2x) = \tan(2x) [/tex]
[tex]\qquad \sf \dashrightarrow \: f(2x) = \dfrac{2 \tan(x) }{1 - { \tan {}^{2} (x) }^{} } [/tex]
replace tan(x) with f(x) in the given equation ~
[tex]\qquad \sf \dashrightarrow \: f(2x) = \dfrac{2 (f(x) )}{1 - { (f {}^{} (x)) {}^{2} }^{} } [/tex]
The expression that was proved is [tex]tan2x=\frac{2[f(x)]}{1-[f(x)^2]}[/tex]
Double angle of function
Given the trigonometry identity
f(x) = tanx
f(2x) tan2x
From double angle theorem;
[tex]tan2x=\frac{tanx+tanx}{1-tanx(tanx)} \\tan2x=\frac{2tanx}{1-tan^2x}[/tex]
Since f(x) = tan(x), substitute into the result to have:
[tex]tan2x=\frac{2[f(x)]}{1-[f(x)^2]}[/tex] (Proved)
Learn more on double angle here: https://brainly.com/question/14691